STUDENTS’ STRATEGIES IN WRITING PROPOSAL THESIS AT ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF KHAIRUN UNIVERSITY - M. Junaidi Usman; Asrul M. Syawal; Naniek Jusnita (Cakrawala Bahasa, 2023)
The purpose of this study was to know the students’ strategies in writing proposal thesis at English Study Program of Khairun University. This study uses a qualitative method. Ten students participated in this research. The data analyzed was used contend analyze and the data collection technique used in this study was interviewed. the result showed that There were 8 out of 10 respondents involved in this research are able to determine their strategies and concepts used in writing proposal thesis then also from 2 out of 10 respondents did not have the strategies or concepts that used in writing proposal thesis and in writing proposal thesis most of students obtained score 42% which is known as pre writing strategy then the second, students obtained score 33% which is known as while writing strategy and the third students obtained 25 which is known as post writing strategy.